(untitled) (American Journal of Pedagogical and Educational Research, 2026)
This article explores how 19th-century Russian literature continues to shape contemporary worldviews, examining its philosophical depth, psychological insights, and moral dilemmas. It highlights the enduring relevance of Russian classics in understanding human nature and societal complexities in the modern era. By analyzing the works of masters such as Dostoevsky, Tolstoy and Turgenev, the study demonstrates how their explorations of guilt and faith provide a mirror for the ethical challenges of the 21st century. Ultimately, it reveals that the 19th-century “Golden Age” remains a vital source of wisdom for navigating today’s existential anxieties.